2018
DOI: 10.1080/01443615.2017.1394280
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison between maternal and neonatal outcome of PPROM in the cases of amniotic fluid index (AFI) of more and less than 5 cm

Abstract: The study was performed on pregnant women with a gestational age of 26-32 weeks of pregnancy, who had been admitted to the hospital with a confirmed diagnosis of premature rupture of membranes. In all eligible women, ultrasounds were performed for the evaluation of amniotic fluid index. Then, the women were divided into two groups according to amniotic fluid index of ≥5 cm and <5 cm. These women were followed and monitored up to delivery. The women of the two groups did not have significant difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 24 publications
3
17
4
Order By: Relevance
“…Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al . and Mousavi et al . In the present study, the cut‐off value of AFI for lowest neonatal mortality was 5.05 cm using ROC curve analysis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al . and Mousavi et al . In the present study, the cut‐off value of AFI for lowest neonatal mortality was 5.05 cm using ROC curve analysis.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies. 3 Furthermore, the results from the present study revealed that oligohydramnios was a risk factor for neonatal mortality, which is consistent with two recent studies by Souza et al 3 and Mousavi et al 22 In the present study, the cut-off value of AFI for lowest neonatal mortality was 5.05 cm using ROC curve analysis. This finding is consistent with the definition of oligohydramnios as an AFI less than 5 cm.…”
Section: Univariable Logistic Regression Multivariable Logistic Regresupporting
confidence: 93%
“…Current evidence has shown the higher risk of RDS in infants with placental abruption, and it is already known that CA decreases the risk of RDS (36,37). In contrast, we did not find any relationship between CA and risk of RDS (26,38).…”
Section: Discussioncontrasting
confidence: 93%
“…Infectious and inflammatory events such as clinical CA may be a risk factor for NEC, IVH, and PDA (26,46,47). However, as supported with our results, CA might not always be related to severe morbidities like NEC, IVH, PDA and mortality (26,28,38,48). Retinopathy of prematurity is another adverse effect of preterm delivery that is particularly related to inflammatory lesions in the placenta (3).…”
Section: Discussionsupporting
confidence: 71%
“…journals.viamedica.pl/ginekologia_polska AFI < 5 cm vs AFI > 5 cm groups, whereas a higher frequency of 1-min Apgar scores < 7, neonatal sepsis and early neonatal mortality in AFI < 3 cm vs AFI > 3 cm groups [8]. Association of AFI scores < 5 cm with increased risk of chorioamnionitis and early onset neonatal sepsis [20,21] as well as an association of AFI scores with APGAR scores, neonatal respiratory distress syndrome and maternal chorioamnionitis [15] were also reported in other studies.…”
Section: Discussionmentioning
confidence: 99%